Ekologi dan Dimensi Pengelolaan Keberlanjutan Mangrove (Studi Kasus Lokasi Ekowisata Guraping, Kota Tidore Kepulauan, Maluku Utara) - Paembonan, Rustam Effendi; Akbar, Nebuchadnezzar; Ibrahim, Abjan; Tahir, Irmalita; Baksir, Abdurrachman; Marus, Ikbal; Najamuddin, Najamuddin; Ismail, Firdaut; Wibowo, Eko S; Siolimbona, Abdul Ajiz; Harahap, Zulhan Arifin; Mutmainnah, Mutmainnah; Angkotasan, Abdul Motalib; Zamani, Neviaty P; Arafat, Dondy; Subhan, Beginer; Natih, Nyoman MN; Rahman, Rahman; Rahimah, Insaniah; Harahap, Zulham Apandy (Jurnal Sumberdaya Akuatik Indopasifik, 2024)
The mangrove ecosystem is a potential coastal and marine area that has a very important resource function. The mangrove ecosystem must be managed sustainably so that it can provide optimal benefits, especially the mangrove ecosystem in Guraping Village which has been designated as an ecotourism area. The aim of this research is to analyze the ecological condition of the mangrove ecosystem and analyze the dimensions of sustainable management of the mangrove ecosystem in Guraping Village. The method used in this research line transect method with a 10x10 meter quadrant to determine ecological conditions. Interviews were conducted with key respondents from stakeholders and the dimensions of sustainable management were analyzed using Rapfish. Measurement of environmental parameters directly on site. The results obtained from this research can determine the ecological condition of mangroves at the research location which still have good status based on the number of species, species density, species cover, diversity index, mangrove canopy cover data. The calculation of the results of the assessment of the dimensions of mangrove sustainability management, which consists of ecological dimensions, economic dimensions, socio-cultural dimensions, legal, institutional and policy dimensions and technological and infrastructure dimensions, is classified as a less accountable level category.